Should we ban total phenolics and antioxidant screening methods? The link between antioxidant potential and activation of NF-κB using phenolic compounds from grape by-products. (30th August 2019) - de Camargo, Adriano Costa; Biasoto, Aline Camarão Telles; Schwember, Andrés R.; Granato, Daniel; Rasera, Gabriela Boscariol; Franchin, Marcelo; Rosalen, Pedro L.; Alencar, Severino Matias; Shahidi, Fereidoon
Highlights: Investigating the validity of colorimetric methods to screen phenolic bioactives. Identification and quantification of phenolics from grape processing by-products. Peroxyl radical and ferric ion as oxidants of biological importance. Reduction of NF-κB activation was anticipated by ORAC and FRAP assays. Decrease in the activation of NF-κB may be attributed to antioxidant pre-treatment. Abstract: Free radical imbalance is associated with several chronic diseases. However, recent controversies have put in check the validity of colorimetric methods to screen the functionality of polyphenols. Therefore, in this study two antioxidant methods, based on chemical reactions, were tested for their ability in anticipating the reduction of the activation of NF-κB using LPS-activated RAW 264.7 macrophages, selected as a biological model. Grape processing by-products from winemaking showed higher total phenolic content (TPC), antioxidant capacity towards peroxyl radical (31.1%) as well as reducing power (39.5%) than those of grape juice by-products. The same trend was observed when these samples were tested against LPS-activated RAW 264.7 macrophages by reducing the activation NF-κB. Feedstocks containing higher TPC and corresponding ORAC and FRAP results translated to higher reduction in the activation of NF-κB (36.5%). Therefore, this contribution demonstrates that colorimetric methods are still important screening tools owing their simplicity and widespread application.